The Murchison Widefield Array Transients Survey (MWATS). A search for low-frequency variability in a bright Southern hemisphere sample. Issue 2 (18th October 2018) - Bell, M E; Murphy, Tara; Hancock, P J; Callingham, J R; Johnston, S; Kaplan, D L; Hunstead, R W; Sadler, E M; Croft, S; White, S V; Hurley-Walker, N; Chhetri, R; et al.
ABSTRACT: We report on a search for low-frequency radio variability in 944 bright (>4 Jy at 154 MHz) unresolved, extragalactic radio sources monitored monthly for several years with the Murchison Widefield Array. In the majority of sources, we find very low levels of variability with typical modulation indices <5 per cent. We detect 15 candidate low-frequency variables that show significant long-term variability (>2.8 yr) with time-averaged modulation indicesM=3.1\!-\! 7.1 per cent. With 7/15 of these variable sources having peaked spectral energy distributions, and only 5.7 per cent of the overall sample having peaked spectra, we find an increase in the prevalence of variability in this spectral class. We conclude that the variability seen in this survey is most probably a consequence of refractive interstellar scintillation and that these objects must have the majority of their flux density contained within angular diameters less than 50 milliarcsec (which we support with multiwavelength data). At 154 MHz, we demonstrate that interstellar scintillation time-scales become long (∼decades) and have low modulation indices, while synchrotron-driven variability can only produce dynamic changes on time-scales of hundreds of years, with flux density changes less than one milli-jansky (without relativistic boosting). From this work, we infer that the low-frequency extragalactic southern sky, as seen by SKA-Low, will be non-variable on time-scales shorter than 1 yr.